Analytical study on the effectiveness of hybrid FRP strengthening on behaviour of slender reinforced concrete square columns. (October 2021) - Saini, Amit; Prakash, S. Suriya
Abstract: Strengthening of reinforced concrete (RC) columns using external bonded (EB) fibre-reinforced polymer (FRP) composites has become popular since last three decades. The effectiveness of EB confinement reduces for slender columns due to the secondary moment arising from applied axial loads. The effectiveness of the hybrid FRP strengthening system for enhancing the performance of RC slender square columns is analytically investigated. Hybrid FRP strengthening uses a combination of EB FRP wrapping for confinement and longitudinal near-surface mounted (NSM) FRP laminates for bending. Hybrid FRP strengthening aims to reduce the second-order lateral displacement of the slender RC column and increase its axial capacity and flexural stiffness. A numerical modelling approach is presented to capture second-order effects in hybrid FRP strengthened slender RC square column based on Newmark's central difference scheme. Both material and geometric nonlinearities are accounted for in the calculations. The predictions are validated with test results available in the literature. After validation, a parametric study is carried out to evaluate the influence of slenderness ratio, the number of EB FRP layers, NSM laminate ratio, modulus of NSM laminate, and buckling of FRP composites. Results show that hybrid FRP strengthening is effective in improving the performance of slender RC columns.